Penerapan Prinsip Good Corporate Governance terhadap Pemenuhan Hak Pekerja - Diandra Adristiara (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
The principle of Good Corporate Governance, is a guideline or reference for running a company in a structured and effective manner in order to create a company that can survive and be sustainable. The application of the principle of Good Corporate Governance in a company will certainly have an impact on the interests of the parties, one of which is the workers in the company. Therefore, to manage and run a company properly, it must be based on the principle of Good Corporate Governance as a guideline so that the company can be run optimally and not in conflict with laws and regulations so that workers' rights can be fulfilled. The purpose of this study is to determine the application of the principle of Good Corporate Governance in accordance with laws and regulations in Indonesia regarding the fulfillment of workers' rights. The research method used in this article is a normative legal approach by reviewing and analyzing laws and regulations and legal literature related to workers' rights and the principle of Good Corporate Governance. The influence of the application of the principle of Good Corporate Governance on the fulfillment of workers' rights is closely related. The application of the principle of Good Corporate Governance will have an impact on workers' rights being fulfilled so that workers' welfare can be guaranteed.